The AMAGAMI technique: an easy technique to achieve precise stapling in thoracoscopic segmentectomy - Sato, Masaaki (J Thorac Dis, 2019)
The “AMAGAMI” or “incomplete grasping” technique is used to adjust the location of the lung while gently grasping the lung tissue with a stapler. Thoracoscopic segmentectomy requires precise but complex stapling, while the surgical view and the number of available instruments are limited. In the AMAGAMI technique, instead of moving the stapler to the targeted position of the lung tissue, an unlocked stapler is used to hold the lung tissue at an easily accessible position, and the lung tissue can then be slid to the ideal resection line using forceps. To use the AMAGAMI technique effectively, “standing stitches” are very helpful in enabling visualization of the ideal resection lines. Standing stitches are placed along intersegmental lines that have been determined based on the information provided by virtual-assisted lung mapping (VAL-MAP) or other marking techniques; these stiches are usually placed at the corner of the targeted segment and in-between if necessary. Monofilament suture is used for standing stitches, and about 1 cm lengths are left to enable later visualization. As these stitches stick out of the lung surface even when viewed from a tangential angle, the direction of stapling is easily visualized in thoracoscopic surgery. These techniques are particularly useful in challenging segmentectomy requiring complex staple lines, such as S10 segmentectomy, and in surgery with limited instrumental access, such as uniportal thoracoscopic surgery.